A new approach to compute grounding impedance of rods in a frequency dependent multi-layer soil - Araujo, Anderson R. J.; Colqui, Jaimis S. L. [UNESP]; Kurokawa, Sergio [UNESP]; Pissolato, Jose (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Long cylindrical rods are commonly employed to grounding system in transmission lines and they can be buried in stratified soils. In this condition, the grounding impedance is significantly modified by the presence of another layer of soil where analytical formulae are not found in literature. Additionally, frequency dependence of soil parameters (resistivity \rho and permittivity \varepsilon) is an important effect that has to be taken in to account for a precise electromagnetic analysis. To tackle these problems, a new approach is proposed to compute grounding impedance of vertical rods buried in a stratified soil. This approach is based on the equivalent quadripole representation rod seen as short transmission lines in each layer of ground. In this paper, the frequency dependence of soil parameters is considered individually in soil composed by several layers of ground. This approach is compared with numerical and analytical methods proposed in the literature and has presented a good agreement. Simulation results show that adding another layer of soil and considering the frequency dependence of electrical parameters of soil cause a significant reduction in the voltage peaks of GPR (Grounding Potential Rise) waveforms.